HOW IS THE LOYALTY OF TELKOMCEL CUSTOMERS IN TIMOR-LESTE? - Raharjo, Luis Ricardo Masri Pakik Budi; Susan, Marcellia (Jurnal Ilmiah Manajemen, Ekonomi, & Akuntansi (MEA), 2022)
This study aims to assess the loyalty of the Telkomcel customers in Timor-Leste through the service and product quality they received mediated by their satisfaction level. Telkomcel is a telecommunication service that provides internet service in Timor-Leste’s urban area. During the covid-19 pandemic, there was a trend of increasing internet users in Timor-Leste due to the movement restriction in Timor-Leste. The object of the study in this research is the individual customer of Telkomcel, which has used Telkomcel for more than three months and has purchased the internet package more than three times. During the data collection, the research managed to collect 160 samples, with 138 samples being valid. Using SmartPLS 3, the Partial Least Square-Structural Equation Modelling (PLS-SEM) technique was used in this work. The results of this study showed that satisfaction had the most significant influence on customer loyalty, followed by service quality and product quality. The customer emphasized the need to enhance Telkomcel service quality as well as their frustration with the slow network connection and internet speed.